Influence of musical-rhythmic means education on the level of development of artistic athletes 6-8 years in rhythmic gymnastics - Alla Mullagіldіna; Iryna Bilenka; Nadiia Kobelieva (Kharkiv State Academy of Physical Culture, 2018)
Purpose: investigate the impact of musical rhythmic education on the development of artistic abilities of gymnasts 6-8 years. Material & Methods: study involved 20 gymnasts aged 6-8 years who are trained at the initial training stage in the Youth Sport School of rhythmic gymnastics. During the study, the following methods were used: theoretical analysis and synthesis of scientific and methodical literature; pedagogical observation; pedagogical testing; pedagogical experiment and methods of mathematical statistics. Results: analysis of the development of artistry showed that by all criteria the average scores in the group corresponded to the average level: plasticity - 3,3 points; expressiveness - 3,2 points; rhythm - 3,0 points; dancing - 3,4 points. Conclusion: as a result of the introduction of various methods and means of musical rhythmic education, the improvement of indicators was established, namely, the plasticity of movements increased by 1,0 points, expressiveness - by 1,4 points, rhythm - 1,5 points, by dancing - 1,1 points.